UPAYA MENINGKATAN PEMAHAMAN MATERI NORMA DAN ATURAN DI MASYARAKAT MELALUI MEDIA PANORAMA PADA MATA PELAJARAN PANCASILA SISWA KELAS V B SD NEGERI 060912 MEDAN - Rosalya Marbun; Chairannisa Amelia; Jamilah Farah Dhiba (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
With reference to Norms and Rules in Society in particular, the goal of this study is to improve students' understanding of Pancasila education material utilising the panoramic medium of class V B at SD Country 060912 Medan. "Panorama" media (Norm-Rule Board in the Community) will be employed to carry out this research. The three phases of PTK (classroom action research), the methodology employed in this study, are Pre-cycle, Cycle I, and Cycle II. The data for this study were gathered through testing, documentation, and observation. Class V B of SD Negeri 060912 Medan Denai has 32 pupils.18 of whom are male and 14 of whom are female, who are the subjects of this study. The study's findings demonstrate the efforts made to help Class VB students at SD Negeri 060912 Medan better understand social norms and rules using panoramic media in Pancasila subjects. This is seen from the fact that 41% of the 13 students in the first cycle were able to reach the required level of subject knowledge. There were 28 pupils, or around 84% of the total, who saw an increase in the second cycle. The data analysis of the study shows that the proportion of students who have not reached the level of completion of learning outcomes has decreased from 59% to 16%. According to this percentage, the use of "Panorama" media in the VB class of SD Negeri 060912 Medan's Pancasila Education theme has completed the entirety of students' comprehension of the curriculum in the 2024–2025 school year.